Consumer ethnocentrism among Malaysians towards purchasing automobile / Adibah Abdul Talib and Amalina Shamsul Kahar - Abdul Talib, Adibah; Shamsul Kahar, Amalina (Faculty of Business and Management, 2014)
This study attempts to identify consumer ethnocentrism among Malaysians towards purchasing automobile by taking the employees of SKF Bearing Industries (Malaysia) Sdn. Bhd. As our respondents. The objectives of this study are to investigate the level of consumer ethnocentrism, factors influencing consumer ethnocentrism and the most significant factors contribute to consumer ethnocentrism among the respondents. Questionnaire is the research tool used in this study. Based on the respondents’ response, the consumer ethnocentrism level among the respondents is moderate. This study revealed that the factors influencing consumer ethnocentrism among the respondents are price, brand image and promotion. Brand image is identified as the most significant factor to consumer ethnocentrism.